Use of Bimetallic Nanoparticles in the Synthesis of Heterocyclic Molecules - Poonam; Singh, Ram (Current Organic Chemistry, 2021)
The heterocyclic molecules are medicinally important and are applied in different other fields. The environmentally benign synthetic method for the synthesis of this important group of compounds is always explored. Bimetallic nanoparticles are getting attention as heterogeneous catalysts for their synthesis. The bimetallic nanoparticles have been usually synthesized by chemical or physical methods or both in combination. Chemists are also using part of plants in the synthesis of bimetallic nanoparticles and these have been successful. The present review work will be going to enrich the existing literature by compiling the use of plant parts in the synthesis of bimetallic nanoparticles and their utility in the synthesis of heterocyclic molecules.
Keywords: Bimetallic